Low genetic diversity in Wolbachia-Infected Culex quinquefasciatus (Diptera: Culicidae) from Brazil and Argentina - Morais, Sirlei Antunes; Almeida, Fábio de; Suesdek, Lincoln; Marrelli, Mauro Toledo (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
Culex quinquefasciatus is a vector of human pathogens, including filarial nematodes and several viruses. Although its epidemiological relevance is known to vary across geographical regions, an understanding of its population genetic structure is still incipient. In light of this, we evaluated the genetic diversity of Cx. quinquefasciatus and Cx. pipiens x Cx. quinquefasciatus hybrids collected from nine localities in Brazil and one site in Argentina. We used mitochondrial genes cox1 and nd4, along with the coxA and wsp genes of the maternally-inherited Wolbachia endosymbiont. The nd4 fragment was invariant between samples, whilst cox1 exhibited four haplotypes that separated two types of Cx. quinquefasciatus, one clustered in southern Brazil. Low sequence diversity was generally observed, being discussed. Both Brazilian and Argentinian mosquitoes were infected with a single Wolbachia strain. As reported in previous studies with these populations, cox1 and nd4 diversity is not congruent with the population structure revealed by nuclear markers or alar morphology. Future Cx. quinquefasciatus research should, if possible, evaluate mtDNA diversity in light of other markers.